(untitled) (CIPEEX, 2022)
THE PRESENT WORK DEALS WITH A REPORT OF EXPERIENCE, WHICH AIMS TO DESCRIBE THE WORK THAT WAS PERFORMED BY UNIEVANGLICA DENTISTRY TEAM DURING FOUR DAYS IN THE COMMUNITY OF. IN THE MUNICIPALITY OF CAAPIRANGA - AM. THE ACTION STRATEGY ADOPTED BY THE DENTISTRY TEAM INVOLVED BOTH THE PREVENTION PART WITH ORAL HYGIENE ORIENTATION AND PROPHYLAXIS, AS WELL AS THE RESTORATIVE AND SURGICAL PART, IN ORDER TO BE ABLE TO REMEDY MOST OF THE PROBLEMS OF ORAL HEALTH OF PATIENTS WHO WERE IN ORDER TO COMPLETE ALL INITIALIZED TREATMENTS. THE SERVICES WERE PROVIDED IN THE BOAT ITSELF, SINCE IT OFFERED THE NECESSARY STRUCTURE FOR THIS, WITH DENTAL EQUIPMENT BROUGHT BY THE INSTITUTION, AS WELL AS SUPPLY OF DENTAL MATERIALS FOR USE IN THE RIVERSIDE POPULATION. DURING THE FOUR DAYS A TOTAL OF 103 (ONE HUNDRED AND THREE) PATIENTS WERE ATTENDED AND 245 (TWO HUNDRED AND FORTY FIVE) PROCEDURES WERE PERFORMED, MOST OF WHICH WERE CLEANINGS AND RESTORATIVE TREATMENTS, OBTAINING AS A RESULT EACH PLANNING OF THIS TYPE OF SOCIAL ACTION , THE PROOF OF THE SUCCESS OF THE PROJECT AND THE PREVENTIVE ACTIONS THAT WERE TAKEN IN PREVIOUS YEARS. SUPERVISED BRUSHING, CARRIED OUT AT THE LOCAL SCHOOL, WAS ATTENDED BY THE MAJORITY POPULATION, WHO WAS ABLE TO LEARN A LITTLE MORE ABOUT HOW TO IMPROVE ORAL HYGIENE. IN THIS SENSE, THE ACTION WAS SUCCESSFUL, ONCE ALL THE TREATMENTS WERE COMPLETED AS WELL AS THE POPULATION COMMITMENT IN RELATION TO THE CONCERN OF IMPROVING THEIR ORAL HEALTH. &NBSP; PALAVRAS-CHAVE (OU KEYWORDS, OU PALABRAS CLAVE): HEALTH PROMOTION. HEALTH PREVENTION. ORAL HEALTH.